Pictorial illusionism : the theatre of Steele MacKaye - Sokalski, J. A. (Joseph Anton), 1962- (McGill-Queen's University Press, 2007)
Drawing together a wealth of primary sources, J.A. Sokalski examines the aims, inventions, and methods of the pictorial style that defined MacKaye's art. Sokalski shows how MacKaye's famous Madison Square Theatre, which featured a double stage reminiscent of an elevator, created whirling pictorial illusions for fashionable New York. He argues that MacKaye's infamous failure, the colossal Spectatorium theatre for the 1893 Chicago World's Fair, was the most complete realization of this illusionary aesthetic. Sokalski also explores MacKaye's influence on Buffalo Bill Cody and how civil war cycloramas expanded his concept of pictorial space.